Community-based economic empowerment strategy for the indigenous seven tribes in Mimika Regency (case study on YPMAK) - Afila Selpina Waroi; Hasan Basri Umar; Risky Novan Ngutra (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the community-based economic empowerment strategies implemented by the Amungme and Kamoro Community Empowerment Foundation (YPMAK) for the seven indigenous tribes in Mimika Regency. The research focuses on how these strategies improve economic independence and overall welfare. Research Methodology: Using a qualitative case study design, data were collected through in-depth interviews, observations, and document analysis with key stakeholders. SWOT analysis was employed to evaluate YPMAK’s strategies by identifying strengths, weaknesses, opportunities, and threats in program implementation. Results: YPMAK’s programs have enhanced community welfare through vocational training, entrepreneurship development, institutional strengthening, and cultural preservation. Local economic development initiatives in agriculture, fisheries, handicrafts, and tourism created new opportunities. However, challenges remain in terms of financial literacy, managerial skills, market access, infrastructure, and reliance on external assistance, limiting the full realization of independence. Conclusions: The YPMAK empowerment strategy positively impacted the welfare of Mimika’s seven indigenous tribes by combining human resource development, institutional support, and local resource utilization. Yet, barriers in financial literacy, infrastructure, and market integration persist, necessitating ongoing collaboration and refinement to achieve sustainable outcomes. Limitations: The study’s qualitative focus and context-specific scope limit the generalizability of findings and restrict quantitative measurement of economic outcomes. Contribution: This research contributes empirical insights into grassroots empowerment models tailored to cultural contexts. It underscores the importance of integrating traditional institutions, local resources, and participatory approaches in designing sustainable development strategies for indigenous communities.